Status and Countermeasures of Art Education in Primary and Secondary Schools in Ethnic Minority Areas - LIU, YUHAN (Pacific International Journal, 2023)
Fine art is a crucial discipline within the field of aesthetics, and fine art education serves as a significant component of aesthetic education. It holds great importance in providing a comprehensive education and fostering the holistic development and well-being of primary and secondary school students. The deficiency in fine art education within primary and secondary schools located in ethnic minority areas necessitates that teachers acknowledge these gaps, analyze their underlying causes, and explore effective measures to promote its development. Revitalizing fine art education is both the mission and responsibility of schools and teachers, as well as a shared aspiration of all sectors of society. In order to achieve this, teachers must enhance their ideological awareness, innovate institutional mechanisms, foster integration and collaboration, and prioritize and strengthen fine art education. Furthermore, it is essential to identify gaps, address deficiencies, increase investment in education, and expand access to high-quality resources. Leveraging the cultural characteristics of ethnic minorities, schools should develop curriculum that is tailored to their specific needs. Additionally, efforts should be made to enrich the teaching force and elevate teaching standards, including forging partnerships with local universities to enhance the professionalism of fine art teachers and strengthen the collective capacity. This study focuses on the current state of fine art education in primary and secondary schools within the Enshi Grand Canyon Scenic Area Administration in Enshi City, Tujia and Miao Autonomous Prefecture, Hubei Province. By utilizing interviews and documentary analysis, the author examines and dissects a primary and secondary school located in a remote town. The aim is to reflect upon and analyze the existing conditions and challenges of fine art education in primary and secondary schools within ethnic minority areas, explore novel ideas in fine art education, and propose measures for improvement and advancement.